2020
DOI: 10.1097/pr9.0000000000000822
|View full text |Cite
|
Sign up to set email alerts
|

Challenges in pain assessment and management among individuals with intellectual and developmental disabilities

Abstract: Introduction: Intellectual and developmental disabilities (IDD) include conditions associated with physical, learning, language, behavioural, and/or intellectual impairment. Pain is a common and debilitating secondary condition compromising functional abilities and quality of life. Objectives: This article addresses scientific and clinical challenges in pain assessment and management in individuals with severe IDD. Meth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
78
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 55 publications
(79 citation statements)
references
References 57 publications
1
78
0
Order By: Relevance
“…Furthermore, the prevalence of chronic pain among individuals with IDD, reaching up to 70%, is high by any standard [ 13 , 15 , 16 ]. Identifying and quantifying pain states among individuals with IDD in a manner that does not necessitate self-reporting is thus crucial in order to provide them with adequate pain management; however, it is also particularly challenging (for a review, see reference [ 17 ]).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the prevalence of chronic pain among individuals with IDD, reaching up to 70%, is high by any standard [ 13 , 15 , 16 ]. Identifying and quantifying pain states among individuals with IDD in a manner that does not necessitate self-reporting is thus crucial in order to provide them with adequate pain management; however, it is also particularly challenging (for a review, see reference [ 17 ]).…”
Section: Introductionmentioning
confidence: 99%
“…Despite longstanding beliefs about pain insensitivity or indifference in persons with intellectual disabilities [ 21 , 22 ], none of the respondents believed that children with PIMD experienced pain less than typically developing children. Our findings are in line with those of Valkenburg et al [ 15 ], who found that around 60% of anaesthetists considered children with intellectual disabilities equally sensitive and 30% considered them more sensitive to pain than typically developing children.…”
Section: Discussionmentioning
confidence: 99%
“…Up to three-quarters estimated that they were not sufficiently trained to confidently care for these children, most of their knowledge being acquired informally through on-the-job training and through mentorship. If children with PIMD have strongly limited communication capabilities, with a restricted, if not absent, ability to self-report pain, physicians should always explore limited self-reporting as a possible means of collecting pain information [ 21 ]. Pain may also prove difficult to distinguish from other conditions, such as distress, anger, sadness or anxiety, even for familiar caregivers, with an overlap in expressed behaviours [ 38 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Besides, special education for caregivers should be offered for better assessment of the pain and delivering the information of the relevant physicians for accurate diagnosis and better management. 32 In addition to the many challenges in assessment, there are also various challenges and difficulties in the management and research regarding pain during childhood. Many concerns regarding this field investigation as the potential presence of biased information, the presence of inadequate sample size, and proper study designs, in addition to exploring the potential mechanisms for proper identification and diagnosis of the pain and eliminating its origin.…”
Section: Challenges Of Pain Assessment In Childrenmentioning
confidence: 99%